Application of Civics Learning Using the Think-Pair-Share Method in Improving Student Understanding - Muhammad Kholil; Fathor Rozi; Nur Hayati (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze and examine the application of Civics learning using the Think-Pair-Share method in increasing student understanding. This research uses a qualitative approach. This research was conducted at a formal institution located in the probolinggo area of MI Raudlatul faizin Hamlet of Karanganyar Sokaan Krejengan Probolinggo. Data analysis techniques include data reduction, data display, and conclusions. The results showed that the institution first used the Think-Pair-Share method in Civics learning. The second presentation is carried out using the initial framework of activities, the application of the Think-Pair-Share learning model, and Activity Evaluation. The implications obtained in the application of Civics learning using the Think-Pair-Share Model can develop students' understanding of Civics lessons which are carried out with the tricks and creativity of the teacher using the Think-Pair-Share learning model